2006
DOI: 10.1038/sj.onc.1209959
|View full text |Cite
|
Sign up to set email alerts
|

RIZ1 repression is associated with insulin-like growth factor-1 signaling activation in chronic myeloid leukemia cell lines

Abstract: RIZ1 is a histone methyltransferase whose expression and activity are reduced in many cancers. In chronic myelogenous leukemia (CML), blastic transformation is associated with loss of heterozygosity in the region where RIZ1 is located and with decreased RIZ1 expression. Forced RIZ1 expression in model CML blast crisis (BC) cell lines decreases proliferation, increases apoptosis and enhances differentiation. We characterized molecular mechanisms that may contribute to potential CML tumor suppressor properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 31 publications
(35 reference statements)
3
52
0
Order By: Relevance
“…Many cancer-associated mutations in RIZ affect its HMT activity, suggesting an important role for this activity in suppression of tumor formation (Kim et al, 2003). RIZ1 knockout mice develop B-cell lymphoma (Steele-Perkins et al, 2001), and in chronic myelogenous leukemia (CML), blastic transformation is associated with loss of heterozygosity in the vicinity of RIZ1 and a decrease in RIZ1 expression (Pastural et al, 2007). Overexpression of RIZ1 in a model CML blast crisis cell line also reduced cellular proliferation and enhanced differentiation, confirming a potential tumor suppressor role mediated by RIZ1.…”
Section: Histone Lysine (K) Methyltransferasesmentioning
confidence: 80%
“…Many cancer-associated mutations in RIZ affect its HMT activity, suggesting an important role for this activity in suppression of tumor formation (Kim et al, 2003). RIZ1 knockout mice develop B-cell lymphoma (Steele-Perkins et al, 2001), and in chronic myelogenous leukemia (CML), blastic transformation is associated with loss of heterozygosity in the vicinity of RIZ1 and a decrease in RIZ1 expression (Pastural et al, 2007). Overexpression of RIZ1 in a model CML blast crisis cell line also reduced cellular proliferation and enhanced differentiation, confirming a potential tumor suppressor role mediated by RIZ1.…”
Section: Histone Lysine (K) Methyltransferasesmentioning
confidence: 80%
“…Previously, we showed that an IGF-1R blocking antibody reduces the viability of CML BC cell lines (Pastural et al, 2007). Similarly, AG1024 has been shown to inhibit clonogenic survival, proliferation and xenograft tumor growth, while enhancing apoptosis (Deutsch et al, 2004).…”
Section: Inhibition Of Igf-1 Receptor Decreases Proliferation and Enhmentioning
confidence: 91%
“…Previously, we showed that Riz1 represses IGF-1 expression in CML BC cell lines (Pastural et al, 2007). To examine whether IGF-1 expression is enhanced in CML BC, we performed immunohistochemistry using an anti-IGF-1 antibody to measure IGF-1 expression in matched patient biopsies from CP and BC (Figure 1).…”
Section: Igf-1 Expression Is Increased In CML Blast Crisismentioning
confidence: 99%
See 2 more Smart Citations